Macroeconomic adjustment, trade, and growth : policy analysis using a macroeconomic model of Nigeria - Soludo, Charles Chukwuma (Nairobi : African Economic Research Consortium, 1995)
This research paper present a medium-sized macroeconomic model of the Nigerian economy that incorporates both forward-looking, model-consistent expectations and goods markets.
"March 1995."
Includes bibliographical references (p. [64]-68).
asm; 27/02/19
Loans
Keywords: Structural adjustment (Economic policy); Economic condistions; Trade; Economic growth; Nigeria